FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH PADAT DI DENPASAR TIMUR - Dewa Ayu Posmaningsih (Jurnal Skala Husada : The Journal of Health, 2017)
Abstract:  Urban waste management also has the driving factors and inhibitors in an effort to increase community participation in waste management. The research objective is to find out how much the relationship of factors predisposing, enabling and reinforcing community participation in solid waste management. The design of this study include observational research with cross sectional. The sample size is 180 housewife and the sample was collected through stratified random sampling. The results showed there is a relationship of knowledge and attitudes towards participation in waste management with the knowledge of determination of 20.6% and 24.9% for attitude determination. Facilities management of community participation in waste management with the determination of 36.2%. Relationship local agencies, community leaders and economic benefits of community participation in waste management by local institutions determination of 10.3%, determination of public figures by 8.5%, and the determination of the economic benefits of 35.9%. Facility factors, economic benefits, local institutions, knowledge and attitudes to contribute jointly to the participation of the determination of 65.1%. The conclusions of this study is a factor predisposing, enabling and reinforcing related to public participation. Factors of knowledge, attitudes, facilities, local agencies, and economic benefits together to contribute to community participation. It is recommended that local governments provide guidance to local agencies in participatory planning of environmentally sound and sustainable solid waste management.Keywords: Predisposing, enabling, reinforcement factors, community  participation Abstrak: Pengelolaan sampah perkotaan juga memiliki faktor pendorong dan penghambat dalam upaya untuk meningkatkan partisipasi masyarakat dalam pengelolaan sampah. Tujuan penelitian ini adalah untuk mengetahui seberapa besar hubungan faktor predisposisi, pendukung dan pendorong partisipasi masyarakat dalam pengelolaan sampah. Desain penelitian ini termasuk penelitian observasional dengan cross sectional. Ukuran sampel adalah 180 ibu rumah tangga dan sampel dikumpulkan melalui stratified random sampling. Hasil penelitian menunjukkan ada hubungan pengetahuan dan sikap terhadap partisipasi dalam pengelolaan sampah dengan pengetahuan. Kesimpulan dari penelitian ini adalah faktor predisposisi, pendukung dan pendorong terkait dengan partisipasi masyarakat. Faktor pengetahuan, sikap, fasilitas, lembaga lokal, dan manfaat ekonomi bersama-sama untuk memberikan kontribusi terhadap partisipasi masyarakat. Kepada pemerintah daerah disarankan memberikan bimbingan kepada lembaga lokal dalam perencanaan partisipatif dari pengelolaan sampah yang berwawasan lingkungan dan berkelanjutan.Kata kunci: Faktor predisposisi, pendukung, penguat, partisipasi masyarakat